1998
DOI: 10.1128/aac.42.9.2437
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Liposomal Amphotericin B with Prolonged Circulation in Blood versus Those of AmBisome and Fungizone against Intracellular Candida albicans in Murine Peritoneal Macrophages

Abstract: Activity against intracellular Candida albicans was assessed in C. albicans-infected murine peritoneal macrophages exposed to long-circulating pegylated amphotericin B liposomes (PEG-AMB-LIP), AmBisome, or Fungizone. The level of antifungal activity of Fungizone is much higher than that of AmBisome or PEG-AMB-LIP, while PEG-AMB-LIP and AmBisome show equivalent activity levels. Previous exposure of uninfected macrophages to PEG-AMB-LIP or AmBisome is advantageous for intracellular antifungal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Saponins are natural detergents that are effective antimicrobial, cholesterol-lowering anticancer compounds. In comparison to L-AmB, it conferred a significantly prolonged blood residence time, and displayed dose-independent pharmacokinetics over a large range of dosages (van Etten et al 1998b). The results showed that there were significantly fewer proven breakthrough fungal infections in the AmBisome™ treatment group.…”
Section: Chapter 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins are natural detergents that are effective antimicrobial, cholesterol-lowering anticancer compounds. In comparison to L-AmB, it conferred a significantly prolonged blood residence time, and displayed dose-independent pharmacokinetics over a large range of dosages (van Etten et al 1998b). The results showed that there were significantly fewer proven breakthrough fungal infections in the AmBisome™ treatment group.…”
Section: Chapter 18mentioning
confidence: 99%
“…These compounds chemically related to the triterpenoid group such as Walsh et al (1999) compared AmBisome™ 3 mg/kg/day with Fungizone 1 0.6 mg/kg/day. In a leukopenic mouse model of disseminated candidiasis, PEG L-AmB had enhanced antifungal efficacy as compared to the nonPEGylated product and L-AmB (AmBisome™) (van Etten et al 1995b(van Etten et al , 1998b. van Etten et al (1995b) reported that the therapeutic efficacy of liposomal AmB coated with PEG (PEG-L-AmB) was better than that of AmBisome™ against invasive candidiasis in neutropenic mice.…”
Section: Chapter 18mentioning
confidence: 99%
“…Peritoneal macrophages Cephalothin Liposomes 1983 [102,103] Ampicillin Nanoparticles 1994 [104] 1994 [105] Chitosan 1996 [106] RAW 264.7, intestine 407 cells Ciprofloxacin Nanocapsules 2012 [107] Murine macrophage-like J774A.1 Gentamicin Liposomes 2013 [66] 1998 [65] Salmonella enterica Infected liver and spleen in a murine salmonellosis model Gentamicin Liposomes 2000 [108] J774A.1 macrophage cells Gentamicin Polymer complexes 2009 [109] Listeria monocytogenes Neutrophils Cloxacillin Liposomes 1986 [110] Human THP-1 cells, murine J 774 cells Gentamicin Nanoparticles 2010 [11] Peritoneal macrophages Ampicillin Liposomes 1988 [111] Nanoparticles 1992 [112] Escherichia coli Peritoneal macrophages Streptomycin Liposomes 1983 [113] Brucella abortus Mononuclear leukocytes Gentamicin Liposomes 1985 [114] Peritoneal macrophages 1985 [115] J 774 cells Nanoparticles 1996 [116] J 774 cells 2012 [117] THP-1 cells Micelles 2012 [118] Brucella melitensis THP-1 human monocytes Gentamicin Micro and nanoparticles 2006 [119] Candida albicans Murine peritoneal macrophages Amphotericin Liposomes 1998 [120] Chlamydia trachomatis and Chlamydia pneumoniae HEp2 cells Rifampin, azithromycin Nanoparticles 2011 [121] Toward an optimized treatment of intracellular bacterial infections Review higher with inhaled microparticles as compared with free drugs administered orally or by intracardiac injection.…”
Section: Salmonella Typhimuriummentioning
confidence: 99%
“…In comparison to L-AmB, it conferred a significantly prolonged blood residence time, and displayed dose-independent pharmacokinetics over a large range of dosages (van Etten et al 1998b). In a leukopenic mouse model of disseminated candidiasis, PEG L-AmB had enhanced antifungal efficacy as compared to the nonPEGylated product and L-AmB (AmBisome™) (van Etten et al 1995b(van Etten et al , 1998b. In another study, immunoliposomes of PEG-L-AmB provided enhanced survival and tissue clearance in a murine model of pulmonary aspergillosis (Otsubo et al 1998).…”
Section: Liposomal Formulationsmentioning
confidence: 99%